Bioinspired Soft Robotic Fish for Wireless Underwater Control of Gliding Locomotion. (20th July 2022) - Lee, Jinwoo; Yoon, Yeosang; Park, Huijae; Choi, Joonhwa; Jung, Yeongju; Ko, Seung Hwan; Yeo, Woon-Hong
Abstract : Soft Robots The back cover image shows an untethered soft robotic fish capable of reconstructing the marine vertebrates' effective locomotion and traveling underwater by controlling localized buoyancy with pneumatic actuators. More information can be found in article number 2100271 by Seung Hwan Ko, Woon‐Hong Yeo and co‐workers.